2008
DOI: 10.2478/v10059-008-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and temperamental predictors of field dependence-independence

Abstract: Cognitive and temperamental predictors of field dependence-independence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…It is well known that UFOV decreases with age, revealing reduced speed of information processing, inability to ignore distracters and inability to divide attention (Owsley et al 1991). Our data agree with studies of psychological differentiation attributing visual field independence with resistance to distraction (Bednarek and Orzechowski 2008). These authors point out that visual field independence (analytic reality perception) may imply efficient functioning of selective attention whereas visual fielddependent individuals have less efficient attention mechanisms, which reduce stimulation (thus reinforcing specific cognitive preferences).…”
Section: Age Effect On Frame Of Reference Selectionsupporting
confidence: 91%
“…It is well known that UFOV decreases with age, revealing reduced speed of information processing, inability to ignore distracters and inability to divide attention (Owsley et al 1991). Our data agree with studies of psychological differentiation attributing visual field independence with resistance to distraction (Bednarek and Orzechowski 2008). These authors point out that visual field independence (analytic reality perception) may imply efficient functioning of selective attention whereas visual fielddependent individuals have less efficient attention mechanisms, which reduce stimulation (thus reinforcing specific cognitive preferences).…”
Section: Age Effect On Frame Of Reference Selectionsupporting
confidence: 91%
“…it was difficult for Fd subjects to extract information when faced with tasks containing irrelevant stimuli (guisande, et al, 2007). Bednarek and Orzechowski (2008) confirmed that both temperamental factors (endurance and emotional reactivity) and cognitive factors (efficiency of selective attention and efficiency of visual-spatial sketch pad) were significant predictors of Fdi. This finding indicated that both the structure of temperament traits and cognitive mechanisms were tapped in tasks used to measure fDI.…”
Section: Field-dependent/-independent Cognitive Style and Mathematicasupporting
confidence: 53%
“…according to Rittschof (2010), the emphasis of cognitive load theory on working-memory capacity may provide a connection between cognitiveload theory and Fdi studies, particularly those involving visual-spatial materials. however, Fdi cannot be explained simply as the effect of individual differences in the efficiency of working memory (see dassonville, walters, & Lunger, 2006) because intelligence and attentional functioning have been shown to be rudimentary cognitive factors (e.g., amador-Campos & Kirchner-nebot, 1999;Richardson & Turner, 2000;guisande, Páramo, Tinajero, & almeida, 2007;Bednarek & Orzechowski, 2008).…”
Section: Field-dependent/-independent Cognitive Style and Mathematicamentioning
confidence: 99%
“…The various styles relate to the thinking behaviors which individuals apply habitually when solving problems, and affect the way in which information is obtained, sorted, and utilized (Birch & Hayward, 1994). More specifi c consideration of recent interpretations of fi eld dependence theory (e.g., Bednarek & Orzechowski, 2008, Guisande et al, 2007 has highlighted how patterns of individual cognitive processing associated with either a fi eld dependent or fi eld independent preference are observable within the present results. The greater number of errors made by participants classifi ed as fi eld dependent demonstrates the dif- fi culty that they may have experienced in identifying the correct movement of the point light image of the dot pattern from the blank black background.…”
Section: Discussionmentioning
confidence: 52%
“…Handal and Herrington (2004) also surmised that the fi eld dependent style may require greater effort and time in the construction of meaningful information when the fi eld lacks structure and few clues are obtainable. The fi eld-independent style is proposed to utilise an active analytic way of perceiving data incorporating better differentiation of fi eld fragments against the entire background, fast scanning of both the entire fi gureground background and criteria for fi eld differentiation (Bednarek & Orzechowski, 2008). Variations in cognitive processing abilities between those that are fi eld dependent and independent may serve as contributing factors in possible individual differences observed in other cognitive abilities (e.g., Guisande, Páramo, Tinajero, & Almeida, 2007).…”
Section: Introductionmentioning
confidence: 99%